Digital technology and psychological happiness: the mediating roles of interpersonal relationships and employment situations - Hu, Wenxin; Zhang, Ziwen; Qu, Xinyue; Mao, Yufei (Frontiers in Psychology, 2024)
Psychological happiness represents the ultimate pursuit of human beings, and the impact of digital technology on psychological happiness is becoming increasingly significant in the era of the digital economy. Based on data from 2020 China Family Panel Studies (CFPS), this study constructs an empirical model that examines the effect and mechanism of digital technology on happiness. Additionally, this study investigates the heterogeneity and robustness of the impact of digital technology on happiness. The research conclusions are as follows: Firstly, digital technology can promote psychological happiness. When controlling for other factors, the marginal effect coefficient of digital technology is 0.031. Secondly, the effect of digital technology on personal happiness varies among different groups, particularly among women, young individuals, primary and college graduates, and rural residents. Furthermore, as absolute income increases, the happiness effect of digital technology diminishes. Thirdly, in terms of the influencing mechanism, digital technology indirectly affects individual happiness by influencing health status, interpersonal relationships, employment situations and income levels. Specifically, digital technology negatively impacts personal health, interpersonal relationships, and agricultural work, while positively impacting family relationships, non-agricultural employment, absolute income and relative income. Digital technology affects happiness through these channels indirectly. Based on the study results, it is proposed that efforts should be made to enhance the development of digital technology infrastructure in remote rural areas, reduce the financial burden associated with digital technology, and promote the digital technology ecosystem. Moreover, providing online services, such as ecommerce, travel reservations, and digital financial management, can improve access to digital technology in rural areas and contribute to increased happiness levels. Simultaneously, there is a need to strengthen digital skills training, particularly among vulnerable populations such as the elderly and rural residents, to improve their proficiency in digital technologies. This can be achieved through the integration of additional educational resources, thereby facilitating cost-free digital technology training and guidance. Meanwhile, it is essential to vigorously develop the new economy and innovative employment models, create job opportunities, foster entrepreneurial prospects, and improve income levels to enhance individual well-being.